2012
DOI: 10.1016/j.crohns.2011.08.019
|View full text |Cite
|
Sign up to set email alerts
|

A chronic care model significantly decreases costs and healthcare utilisation in patients with inflammatory bowel disease

Abstract: Healthcare utilisation and disease burden in IBD decreased significantly since introducing an IBDS. These data suggest that proactive management improved outcomes. Contact with a gastroenterologist and IBDS seemed to give best results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 21 publications
4
86
0
4
Order By: Relevance
“…A formal IBDS was introduced in April 2008 11. This consisted of a dedicated weekly IBD clinic and a joint medical–surgical clinic for IBD patients.…”
Section: Methodsmentioning
confidence: 99%
“…A formal IBDS was introduced in April 2008 11. This consisted of a dedicated weekly IBD clinic and a joint medical–surgical clinic for IBD patients.…”
Section: Methodsmentioning
confidence: 99%
“…Sin duda, la implementación de estas medidas tendrá un significativo impacto en el manejo de los pacientes con EII. Estudios han demostrado que un modelo de atención integrado puede mejorar los resultados clínicos y psicosociales de estos pacientes, siendo incluso costo-efectivo 50 .…”
Section: Calidad De La Atenciónunclassified
“…Compliance with recommended IBD care processes and quality measures are better in an IBD center [16]. Providing the patient and referring physician with a direct dial contact number to the IBD center and IBD nurse specialist can result in decreased visits to the emergency room and improved triage of acutely ill patients [20]. In keeping with the biopsychosocial model, improvements in anxiety, depression, quality of life, and coping skills occur when psychotherapy is provided to IBD patients [15].…”
mentioning
confidence: 93%
“…These studies have shown that patients using an IBD center have decreased hospitalization rates, decreased length of stay and costs of hospitalizations when they occur, and decreased polypharmacy including less opiate and steroid use [15,[18][19][20]. Compliance with recommended IBD care processes and quality measures are better in an IBD center [16].…”
mentioning
confidence: 99%